Attitudes Towards Strangers: a test of Uslaner’s Theory of Generalized Trust - Serrano-Maillo, Alfonso (Tendencias Sociales. Revista de Sociología, 2018)
Uslaner and others predict that generalized trust is an independent construct that does not need to be analyzed solely as an element of social capital. Uslaner’s theory suggests that generalized trust should be measured with a single item about whether most people can be trusted or you can’t be too careful. It is predicted that generalized trust is a predictor of attitudes towards strangers. Uslaner’s theory conjectures that generalized trust is established early in life and that it does not depend on experience, and that variables that do not depend on experience will be better predictors of attitudes towards strangers than those that are influenced by experience. We explore hypotheses derived from Uslaner’s theory of generalized trust with data from Spain collected in the frame of the 7th wave of the European Social Survey. Data analyses rely on standard regression tools. Uslaner y otros predicen que la confianza generalizada es un constructo independiente que no precisa ser analizado únicamente como un elemento del capital social. La teoría de Uslaner sugiere que la confianza generalizada debería medirse con un ítem único sobre si puedes confiar en la mayoría de las personas o si es mejor ser precavido. Se predice que la confianza generalizada es un predictor de las actitudes hacia los extraños. La teoría de Uslaner conjetura que la confianza generalizada queda establecida pronto en la vida de las personas y que no depende de la experiencia, así como que las variables que no dependen de la experiencia serán mejores predictores de las actitudes hacia los extraños que las que se encuentran influenciadas por la experiencia. Exploramos hipótesis derivadas de la teoría de la confianza generalizada de Uslaner con datos de España recogidos en el marco de la 7.ª oleada de la Encuesta Social Europea. Los análisis utilizan herramientas de regresión comunes.